Combined association of socioeconomic status and type 2 diabetes with influenza vaccination in older adults: A cross-sectional analysis of the Korea National Health and Examination Survey (2019–2022) - Sunghak Kim; Kyuwoong Kim (PLoS ONE, 2026)
Background Given the limited evidence on the joint association of socioeconomic status and type 2 diabetes (T2DM) with influenza vaccination uptake, we examined this association among adults aged 65 years and older eligible for the National Immunization Program in the Republic of Korea. Methods We analyzed data from the Korea National Health and Nutrition Examination Survey (KNHANES) 2019–2022, stratified by pre-COVID-19 (2019) and COVID-19 (2020–2022) periods including 5,525 adults aged 65 years and older. The participants were classified by T2DM status and SES indicators (income, education, and economic activity). Multivariable logistic regression estimated adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for influenza vaccination, adjusting for demographic characteristics, health behaviors, health status measures, and healthcare access factors. Results Among 5,525 adults aged ≥65 years in the 2019–2022 Korea National Health and Nutrition Examination Survey, the weighted influenza vaccination rate was 77.6% overall (78.2% pre–COVID-19; 77.1% during COVID-19). Compared with high-income adults without diabetes, low-income adults with T2DM had lower odds of vaccination (adjusted odds ratio [aOR] = 0.75; 95% CI, 0.57–0.99), and low-income adults without T2DM showed a similar trend (aOR = 0.82; 95% CI, 0.65–1.03). By education, low-education adults with T2DM had lower vaccination likelihood (aOR = 0.83; 95% CI, 0.61–1.15) compared with college-educated adults without T2DM. Economic activity was not significantly associated with vaccination (aOR = 0.91; 95% CI, 0.70–1.18). Findings were consistent across pre–COVID-19 and COVID-19 periods ( P for interaction = 0.24). Conclusions Socioeconomic disadvantage and T2DM may jointly contributed to lower influenza-vaccination uptake among Korean adults aged 65 years and older.